2019
DOI: 10.1308/rcsann.2019.0032
|View full text |Cite
|
Sign up to set email alerts
|

The effect of time to surgery on outcomes and complication rates following total hip arthroplasty for fractured neck of femur

Abstract: Introduction Total hip arthroplasty is recommended for elderly patients with fractured neck of femur who are independently mobile, have few co-morbidities and are not cognitively impaired. Providing a daily total hip arthroplasty service is challenging for some units in the UK and considering that these patients may be physiologically distinct from the average hip fracture patient, loss of the best practice tariff as a result of surgical delay may be unjustified. The aim of this study was to determine whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The results supported the former studies of Leer-Salvesen et al, which was also a database investigation of the Norwegian Patient Registry and included 83,727 patients over 10 years [ 19 ]. However, conflicting evidence yielded from the studies of Craik et al [ 20 ] and Lim et al [ 21 ], both of which investigated also an over ten-year period data resulting in no significant differences in regard of complications. The reasons of controversial evidences might be multiple aspects.…”
Section: Discussionmentioning
confidence: 99%
“…The results supported the former studies of Leer-Salvesen et al, which was also a database investigation of the Norwegian Patient Registry and included 83,727 patients over 10 years [ 19 ]. However, conflicting evidence yielded from the studies of Craik et al [ 20 ] and Lim et al [ 21 ], both of which investigated also an over ten-year period data resulting in no significant differences in regard of complications. The reasons of controversial evidences might be multiple aspects.…”
Section: Discussionmentioning
confidence: 99%
“…The results supported the former studies of Leer-Salvesen et al [19], which was also a database investigation of the Norwegian Patient Registry and included 83727 patients over 10 years. However, con icting evidence yielded from the studies of Craik et al [20] and Lim et al [21], both of which investigated also an over ten-year period data resulting in no signi cant differences in regard of complications. The reasons of controversial evidences might be multiple aspects.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal time for surgery associated with the lowest risk of complications after hip fracture surgery has been the subject of numerous studies in the literature. While some authors found advantages for surgery within 24 h, others could not confirm these results [1,17,19,[21][22][23][24][25][26][28][29][30][31][32]35,[42][43][44]. These heterogeneous results thus leave room for interpretation also for national guidelines.…”
Section: The Time To Surgery Interval In Hip Fracturesmentioning
confidence: 99%
“…Many studies revealed predictive factors for the occurrence of perioperative complications after hip fracture, such as gender, age, comorbidities, systemic anticoagulation, and the general physical status at the time of the injury [1,11,17,19,[21][22][23][24][25][26][27][28][29][30][31][32]. The most controversial factor recognized and examined in multiple studies on the therapy of hip fractures is the "time-to-surgery" interval [19,33,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation